2022
DOI: 10.3390/ijerph19095094
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle Prescription for Depression with a Focus on Nature Exposure and Screen Time: A Narrative Review

Abstract: Recent lifestyles changes have favored increased time in contact with screens and a parallel reduction in contact with natural environments. There is growing awareness that nature exposure and screen time are related to depression. So far, the roles of how these environmental lifestyles affect depressive symptoms and disorders have not been reviewed simultaneously. The aim of this review was to gather the literature regarding the role of nature exposure and screen time in depression. An emphasis was made on cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 95 publications
0
3
0
Order By: Relevance
“…Roberts and Helbich (2021) conducted a seven-day smartphone-based tracking study and further pointed out that exposure to green surroundings, both at home and on the road, has been linked to a reduction in depression. Some reviews and metaanalyses also confirmed the association of nature exposure and depressive disorder (Roberts et al, 2019;Jakstis and Fischer, 2021;Balanzá-Martínez and Cervera-Martínez, 2022). For example, a recent meta-analysis reported that short-term contact (10-90 min) with natural spaces is linked to a small decrease in depressive mood (Roberts et al, 2019).…”
Section: Nature Exposure and Depression Among Prisonersmentioning
confidence: 86%
“…Roberts and Helbich (2021) conducted a seven-day smartphone-based tracking study and further pointed out that exposure to green surroundings, both at home and on the road, has been linked to a reduction in depression. Some reviews and metaanalyses also confirmed the association of nature exposure and depressive disorder (Roberts et al, 2019;Jakstis and Fischer, 2021;Balanzá-Martínez and Cervera-Martínez, 2022). For example, a recent meta-analysis reported that short-term contact (10-90 min) with natural spaces is linked to a small decrease in depressive mood (Roberts et al, 2019).…”
Section: Nature Exposure and Depression Among Prisonersmentioning
confidence: 86%
“…The association between behavioral patterns and depression symptoms is probably bidirectional (54). Second, the duration of cohabitation, which is an important confounding factor (55), was not specifically ascertained among our participants. Future research should consider the duration of cohabitation when estimating the association between behavioral patterns and depression.…”
Section: Discussionmentioning
confidence: 98%
“…Future research should consider the duration of cohabitation when estimating the association between behavioral patterns and depression. Third, although we adjusted for as many potential confounders as possible, there are still residual confounders (i.e., mental and physical health, time spent outdoors, and screen time) ( 44 , 56 ). Fourth, we used the PHQ-9 to assess depression symptom.…”
Section: Discussionmentioning
confidence: 99%